Desenvolvimento e caracterização de biomaterial adesivo à base de látex de jaca (Artocarpus heterophyllus) com adição de moléculas bioativas visando o tratamento da periodontite - Lima, Barbara Boralli Tavares de (2024)
Periodontal disease, situated within the context of chronic infectious diseases, represents a significant challenge to oral health due to its inflammatory nature, which compromises the supporting structures of the teeth. While conventional treatment for periodontitis aims to reduce inflammation and bacterial load, regeneration of lost periodontal tissue remains an obstacle due to the limited regenerative capacity of tissues affected by periodontitis. In this context, the present study aimed to develop an adhesive biomaterial composed of jackfruit latex (Artocarpus heterophyllus), incorporated with bioactive substances such as pomegranate dry extract (RO), recognized for its antimicrobial properties, and Simvastatin (SIN), known for its ability to promote osteoconduction. Thus, this work aims to offer an innovative and economically viable alternative for periodontitis treatment. Although the literature still lacks specific data on the application of this biomaterial for this purpose, preliminary studies indicate the promising adhesive properties of LJ. Therefore, the first stage of the project focused on obtaining the adhesive biomaterial composed of jackfruit latex (LJ), as well as the incorporation of different concentrations (1.2%, 2.5%, 5.0%, and 10%) of RO in relation to the mass of LJ. Physicochemical analyses confirmed the presence of RO in LJ samples. The presence of RO did not alter the thermal properties of LJ. Additionally, release analysis revealed a slow-release profile of RO in LJ. Microbiological analyses revealed the antibacterial and bacteriostatic effects of RO against E. coli, S. aureus, and S. oralis. In the second stage, different concentrations of simvastatin (SIN) (3.1; 6.3 and 12.5 µg) were added to the system composed of LJ + RO. The analysis of the physicochemical properties did not show any significant chemical interaction between LJ and RO. On the other hand, the lowest concentration of SIN in LJ + RO showed the best results in the osteoinduction study, indicating its potential as an efficient candidate for the treatment of periodontitis